INTENTION AND EXUBERANCE LEVEL OF ONLINE BUYING BEHAVIOR OF SOCIAL MEDIA MARKETING IN VELLORE CITY - Praveen, R.; Jothiselvamuthu kumar, A. (International Journal of Psychosocial Rehabilitation, 2020)
Buyer gets products not only to accomplish their contemporary needs but also for some reasons and circumstances. Such unplanned purchasing is called impulse buying. Impulse buying describes the behaviors of buyers or shoppers who purchase directly lacking preplan. Social media marketing plays a momentous role in online purchasing nowadays. The aim of the study is to stumble onthe exuberance and intention level of online buying behavior of social media marketing in Vellore City. The main objective of the study is to identify the Intention Level and exuberance level of online buying behavior of social media marketing. Judgment sampling method was used to collect the data. The size of the sample is 180 respondents in Vellore city. The primary data was collected questionnaire from the respondents of Vellore City. For analyzing the primary data, statistical tools such as, Percentage Analysis, Reliability Statistics, Factor analysis, T- test, F- test, Chi-Square Test and One Sample T Test were used with the help of SPSS Software version21.0. There is no significant association between the exuberance level of online buying behavior of social media marketing and their demographic variables.